2002
DOI: 10.1080/01421590220134105
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes among students and teachers on vertical integration between clinical medicine and basic science within a problem-based undergraduate medical curriculum

Abstract: Important elements in the curriculum at the Faculty of Health Sciences in Linköping are vertical integration, i.e. integration between the clinical and basic science sections of the curriculum, and horizontal integration between different subject areas. Integration throughout the whole curriculum is time-consuming for both teachers and students and hard work is required for planning, organization and execution. The aim was to assess the importance of vertical and horizontal integration in an undergraduate medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 6 publications
2
34
0
1
Order By: Relevance
“…More emphasis may be placed on the basic medical sciences in the earlier years and on clinical sciences and the practice of medicine in the later years. 4 Introduction of vertical integration may be considered as one of the major reforms to prepare better physicians for the next century. 5 Vertical integration between basic sciences and clinical medicine has been found to stimulate profound rather than superficial learning, and thereby results in better understanding of important biomedical principles.…”
Section: Introductionmentioning
confidence: 99%
“…More emphasis may be placed on the basic medical sciences in the earlier years and on clinical sciences and the practice of medicine in the later years. 4 Introduction of vertical integration may be considered as one of the major reforms to prepare better physicians for the next century. 5 Vertical integration between basic sciences and clinical medicine has been found to stimulate profound rather than superficial learning, and thereby results in better understanding of important biomedical principles.…”
Section: Introductionmentioning
confidence: 99%
“…15 Much of the focus within studies of integrated curricula is around the perceptions of students or of faculty members 13 and is not specific to pharmacy. 16,17 None of this is to suggest that integrated curricula are ineffective, rather that there is an absence of evidence to prove the benefits of these curricula within healthcare practice. The challenges involved in testing an integrated model with well-designed empirical research projects are significant and require a longitudinal study that includes graduates' early practice years to assess changes in knowledge and competence.…”
Section: Evidence For Integrated Curriculamentioning
confidence: 99%
“….demonstrated a greater understanding of the importance of basic sciences" or that "students as well as teachers appreciated both [horizontal and vertical] forms of integration highly" are encouraging but hardly compelling justification for curriculum change. 48,49 More rigorous studies of learning outcomes of integrated curricula have demonstrated improvements that are modest at best. For example, a study comparing the diagnostic ability of medical students in a traditional curriculum, a problem-based learning curriculum, and a systems-based integrated curriculum showed similar performance by those in the problem-based and the integrated curriculum, both of which were better than performance in the traditional curriculum.…”
Section: Lack Of Evidence Of Effectivenessmentioning
confidence: 99%